E-BOOKS UTILISATION AND STUDENTS' ACADEMIC ACHIEVEMENT IN UNIVERSITIES IN LAGOS STATE, NIGERIA: IMPLICATION FOR EDUCATIONAL PLANNERS - Emmanuel Semako Gbesoevi; Monsurat Lolade Oyelami; Bolanle Adeyemi Ola; Oluwatosin Gabriel Jinodu (International Journal of Educational Best Practices, 2022)
This study examined e-books utilisations and students' academic achievement in universities in Lagos State: implication for educational planners. With the use of descriptive survey research methodologies, this study was driven by three research questions and three null hypotheses. All six of Lagos State's traditional universities make up the study's population. Three institutions were chosen using a straightforward random sampling method. Additionally, 150 final-year students from each of the studied institutions were chosen using a practical selection approach, resulting in 450 respondents from the three universities chosen for the study. A well-structured questionnaire titled "E-Book Utilisation and Students' Academic Achievement in Universities" was used to gather data (IEBSAAU). The test-retest reliability approach was used to validate the instrument, and it was determined to be reliable with a reliability coefficient of 0.79. The statistical technique Chi-Square was used to gather data. The findings showed significant relationship in the use of electronic books with X2 = (4, N = 450) = 246.462, P =.000; a significant relationship between computer literacy with  X2 = (4,  N = 450) = 206.431 , P =.000; a significant relationship between students ‘perception on the use of electronic books for academic progress with  X2 = (4,  N = 450) = 262.109 , P =.000 and student academic achievement. It is recommended that: E-book library should be set up and maintained in every university of study to boost interest and enlightens students and teachers on the importance of e-books to teaching and learning.